Congruencia entre actividad y perfil investigativo de la Universidad Técnica De Manabí con las necesidades empresariales del entorno socioeconómico - Intriago Navarrete, Yordi Gabriel (2021)
The present project aimed to carry out a study on the research activity of the teachers of the Technical University of Manabí (UTM) teachers to determine its congruence with the business needs of the socioeconomic environment. It proceeded from scientific and legal theories that gave credibility to the investigation, the methodology used was observation visits and surveys of the research teachers, consecutively, surveys were applied to key informants from neighboring companies to the institution, with the data obtained, a matrix was elaborated in order to determine the congruence between the scientific activity and the socioeconomic environment from the profile of the researchers and linking purposes, the results of which indicated that 40% of the projects have not been favorable to the development of these organizations located in the Portoviejo canton, in the same way, the key informants of the companies mentioned that it is necessary that they implement plans that are oriented to favor the development of the companies. Regarding the level of acceptance that the university has regarding the promotion of business development, it can be understood through the results that it is in a good standard with 60%, it is concluded that, it is important to maintain and expand the scope of the agreements to improve knowledge transfer, because, in the sectors surrounding the university, there is no evidence of research activities that reduce business needs.